Individual level peer interventions for gay and bisexual men who have sex with men between 2000 and 2020: A scoping review. - Jack Freestone; Krista Joy Siefried; Garrett Prestage; Mohamed Hammoud; Angus Molyneux; Adam Bourne (PLoS ONE)
Background Peer-led interventions are central to the global HIV response for gay and bisexual men who have sex with men [GBMSM]. Since the year 2000, technological advancements in HIV and an increased response to the health disparities faced by GBMSM outside of HIV, have contributed to the expanding scope of their content and delivery. This review sets out to characterise the evidence base for individual level peer interventions for GBMSM, overview approaches to implementing and evaluating them and identify future priorities for their delivery and evaluation. Methods A scoping review methodology was applied and evaluations of peer programs for GBMSM published in peer reviewed journals were identified via subject heading and keyword searches across five electronic databases. Titles and abstracts were reviewed, and full texts were assessed against eligibility criteria. A coding framework was used to extract data from included studies against intervention implementation and evaluation components. Results A total of 38 studies evaluating peer led interventions against effectiveness outcomes were deemed eligible for inclusion and coded into four intervention modalities; peer counselling [n = 6], groupwork programs [n = 15], peer navigation [n = 7] and peer education [n = 10]. Most addressed HIV [n = 32] and across intervention modalities, evaluations demonstrated compelling evidence of significant effect. Intervention effects on broader indicators of psychosocial wellbeing were not extensively evaluated. Expertise regarding the implementation and evaluation of peer interventions addressing HIV among GBMSM ought to be leveraged to expand the scope of peer intervention to meet the diverse health and wellbeing needs of GBMSM.